PENDAMPINGAN PENULISAN HISTORIOGRAFI SITUS CANDI SUROWONO SEBAGAI PENGEMBANGAN PENGAJARAN SEJARAH LOKAL MGMP SMA/MA KOTA KEDIRI - Agus Budianto; Nara Setya Wiratama; Zainal Afandi; Sigit Widiatmoko; Heru Budiono; Yatmin Yatmin; Gusti Garnis Sasmita; Ivrada Setiya Budi; Muhamad Fajrul Al Fauzi (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
Writing history (historiography) of modern Indonesia begins with the desire of historians to implement historical methodology with new patterns in accordance with Indonesia centric. This was due to the fact that the writing style of previous Indonesian history was still heavily oriented towards the Dutch East Indies centric, so there was a need for downward socialization, especially to MGMP SMA/MA teachers in Kediri City. Historiography Writing Assistance at the Surowono Temple Site aims to: (1) improve teachers' skills in good historical writing (historiography) in accordance with the principles of History; (2) increasing teacher expertise in developing local history teaching with the study object of Surowono Temple. The implementation method in this community service activity is the training method, which has several stages starting from design, implementation (lectures, discussions, demonstrations), and evaluation. Participants acquire new skills, especially in historical writing based on the local history of Kediri, namely the Surowono Temple. Participants can read the temple reliefs with a semiotic approach, by comparing them with previous reliefs and making conclusions. Based on the mentoring activities carried out, from 22 MGMP History SMA/MA teachers in Kediri City, it was found that 18 teachers were very satisfied with this activity and were able to complete the task well. The four teachers experienced difficulties in accessing digital resources, so it can be concluded that this mentoring activity was successful.